KONSEP SITE PLAN PERANCANGAN PERPUSTAKAAN BIOKLIMATIK DI PALEMBANG - Putri, D.E.P; Siswanto, Arie; Romdhoni, Muhammad Fajri (Jurusan Teknik Sipil & Perencanaan Fakultas Teknik Universitas Sriwijaya, 2018)
The design of the library inÂ Palembang consider various aspects of them, are tropical climate conditions that have high rainfall, heat and humid air. Macro and micro siting conditions greatly affect the concept of library design. The concept of designing the site for the Library uses the Bioclimatic approach in order to create an element of comfort for building users based on the local climate. The method used in this research is design thinking method which consists of 5 stages of design and perform contextual analysis based on the climate and the characteristics of the site. Before the analysis activity is done, measurement and observation of tread area are included in the site. Based on the results of contextual analysis, the design of the Librarys siteplan can provide responses to the environment, site potential, circulation and accessibility, climatology, noise and pollution, vegetation, people and culture and utilities. The response is a bioclimatic answer to improve thermal and visual comfort associated with the use of vegetation around buildings or public spaces to control wind, materials that do not cause excessive glare in the site, to water around the site to lower the temperature and flood locally. The conclusion is the site plan of the library in Palembang City which has hot weather and high rainfall and humidity can be anticipated to improve the comfort of the building user through the use of contextual climate with the environment of the site based on Bioclimatic principles.